A flexible porous pyrene tetraone-based polyimide composite material, a preparation method and application thereof
Patent Information
- Application Number
- CN202511720917.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-21
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-11-21
AI Technical Summary
然而现有共轭羰基化合物材料都是块状粉末、导电性差,制备电极需要大量导电剂和粘结剂及集流体,致使其实际比容量只能达到理论比容量的一半且稳定性不佳,限制了其进一步发展
[0016] This invention achieves uniform dispersion and controllable construction of porous structures of pyrene-tetraketone-based polyimide through polyimide molecular structure design and vacuum filtration. A flexible porous pyrene-tetraketone-based polyimide composite material is constructed using in-situ composites of highly conductive carbon nanotubes and in-situ integrated graphene oxide. The resulting pyrene-tetraketone-based polyimide composite film exhibits excellent mechanical flexibility and conductivity, with fully exposed active sites of the pyrene-tetraketone-based polyimide. This reduces its solubility in the electrolyte and effectively improves the conductivity of the composite material. Direct application in lithium-ion battery cathode materials effectively shortens the ion/electron conduction distance, thereby improving its capacity performance and cycle life. It achieves high reversible specific capacity, excellent cycle stability, and improved operating voltage, laying a theoretical foundation for the design and development of flexible, high-performance organic cathode materials.
Smart Images

Figure CN121517704B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite materials technology, and in particular to a flexible porous pyrene tetraketone polyimide composite material, its preparation method, and its application. Background Technology
[0002] With the depletion of traditional energy sources such as oil, natural gas, and coal, the development of efficient, clean, and renewable new energy sources has become extremely urgent. Secondary batteries have attracted widespread attention due to their high specific energy and volumetric energy density, portability, and recyclability. Traditional lithium-ion secondary batteries use lithium-intercalated graphite compounds as the negative electrode material, specifically layered compounds like LiMO. x The positive electrode is formed by M, which is Co, Ni, Mn, or Fe, etc. However, the poor overcharge resistance, poor thermal stability, high toxicity, and limited resources of these layered compounds have restricted their further development. Compared with traditional layered inorganic electrode materials, electroactive organic materials have attracted widespread attention at home and abroad in recent years due to their diverse structures, abundant reserves, and environmental friendliness. They can achieve efficient conversion of electrical energy and chemical energy through ion doping and impurity removal. However, small molecule organic electrode materials suffer from several problems, such as low actual charge-discharge efficiency, easy dissolution, poor conductivity, and structural instability. As a result, their actual specific capacity is far lower than the theoretical value, and their rate performance and cycle life are also severely limited, making their practical application in lithium-ion secondary batteries very difficult. Therefore, the development of high-performance organic electrode materials with long cycle life, high conductivity, and structural stability is a research focus and hot topic in the contemporary new energy field.
[0003] Graphene, carbon nanotubes, and other carbon materials are widely used in flexible substrates for energy conversion and storage devices due to their large specific surface area, good conductivity, and excellent mechanical properties. Therefore, the preparation of organic electrode materials by combining graphene, carbon nanotubes, and organic compounds has great application potential in lithium-ion batteries. Among various organic electrode materials, conjugated carbonyl compounds possess advantages such as high theoretical specific capacity, wide availability, and designability, making them a promising candidate for competitive lithium-ion battery electrode materials. However, existing conjugated carbonyl compound materials are all bulk powders with poor conductivity. Electrode preparation requires large amounts of conductive agents, binders, and current collectors, resulting in actual specific capacities that can only reach half of the theoretical specific capacity, and poor stability, thus limiting their further development. Summary of the Invention
[0004] The purpose of this invention is to provide a flexible porous pyrene tetraketone-based polyimide composite material, its preparation method and application, which has high reversible specific capacity and excellent cycle stability.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing a flexible porous pyrene tetraketone-based polyimide composite material, comprising the following steps: 2,7-Diaminopyrene-4,5,9,10-tetraketone, aryltetracarboxylic dianhydride, carbon nanotubes and a first solvent were mixed and subjected to a polycondensation reaction to obtain a pyrene-tetraketone-based polyamic acid / carbon nanotube composite liquid. The pyrene-tetraketone polyamic acid / carbon nanotube composite liquid, graphene oxide, and a second solvent were mixed and then subjected to layer-by-layer self-assembly by vacuum filtration to obtain a pyrene-tetraketone polyamic acid composite film. The pyrene-tetraketone-based polyamic acid composite film was heat-treated to obtain a flexible porous pyrene-tetraketone-based polyimide composite material.
[0006] Preferably, the aryltetracarboxylic dianhydride includes pyromellitic dianhydride, naphthalenetetracarboxylic dianhydride, or perylenetetracarboxylic dianhydride; the first solvent includes DMSO, NMP, or DMAC; and the molar ratio of 2,7-diaminopyrene-4,5,9,10-tetraone to aryltetracarboxylic dianhydride is 1:1 to 1.5.
[0007] Preferably, the mass of the carbon nanotubes is 1 to 10% of the mass of pyrene-tetraketone polyamic acid in the pyrene-tetraketone polyamic acid / carbon nanotube composite solution.
[0008] Preferably, the polycondensation reaction is carried out at a temperature of 160-200°C for 12-24 hours, and in an argon atmosphere.
[0009] Preferably, the mass ratio of pyrene-tetraketone polyamic acid in the graphene oxide and pyrene-tetraketone polyamic acid / carbon nanotube composite solution is 1~5:10, and the second solvent includes methanol, ethanol or acetone.
[0010] Preferably, the conditions for vacuum filtration include: a vacuum degree of -0.03 to -0.1 MPa and a vacuuming time of 10 to 40 min.
[0011] Preferably, the thickness of the pyrene tetraketone polyamic acid composite film is 100~200μm.
[0012] Preferably, the heat treatment temperature is 300~400℃, the time is 2~5h, and the atmosphere is argon; the heating rate to the heat treatment temperature is 1~5℃ / min.
[0013] The present invention provides a flexible porous pyrene tetraketone-based polyimide composite material prepared by the preparation method described above. The pyrene tetraketone-based polyimide is coated on carbon nanotubes and forms a three-dimensional interconnected porous conductive structure with graphene.
[0014] This invention provides the application of the flexible porous pyrene tetraketone-based polyimide composite material described above as a positive electrode material in lithium-ion batteries.
[0015] This invention provides a method for preparing a flexible porous pyrene-tetraketone-based polyimide composite material. The method involves mixing 2,7-diaminopyrene-4,5,9,10-tetraketone with arylic anhydride and carbon nanotubes, followed by in-situ polycondensation to obtain a pyrene-tetraketone-based polyamic acid / carbon nanotube composite liquid. The obtained pyrene-tetraketone-based polyamic acid / carbon nanotube composite liquid is then mixed with a graphene oxide dispersion to form a uniform composite liquid. Vacuum filtration and layer-by-layer self-assembly are then performed to combine carbon nanotubes and graphene oxide to form a flexible three-dimensional network structure of the pyrene-tetraketone-based polyamic acid composite membrane. Finally, an imidization heat treatment is performed to obtain a porous pyrene-tetraketone-based polyimide composite membrane material. This composite material, formed by combining carbon nanotubes and graphene oxide to create a three-dimensional interconnected porous network structure, possesses excellent mechanical flexibility and conductivity. When used as an electrode, it significantly improves the conductivity of polyimide and the exposure of lithium storage active sites. It also facilitates the diffusion and adsorption of electrolyte ions, resulting in excellent reversible specific capacity and cycle stability, making it an ideal high-performance flexible green lithium-ion battery cathode material. This invention utilizes in-situ polymerization and vacuum filtration layer-by-layer self-assembly technology to uniformly and efficiently composite pyrene-tetraketone polyimide with carbon nanotubes and graphene, achieving synergistic reinforcement and preparing a high-performance green flexible lithium-ion battery composite electrode material.
[0016] This invention achieves uniform dispersion and controllable construction of porous structures of pyrene-tetraketone-based polyimide through polyimide molecular structure design and vacuum filtration. A flexible porous pyrene-tetraketone-based polyimide composite material is constructed using in-situ composites of highly conductive carbon nanotubes and in-situ integrated graphene oxide. The resulting pyrene-tetraketone-based polyimide composite film exhibits excellent mechanical flexibility and conductivity, with fully exposed active sites of the pyrene-tetraketone-based polyimide. This reduces its solubility in the electrolyte and effectively improves the conductivity of the composite material. Direct application in lithium-ion battery cathode materials effectively shortens the ion / electron conduction distance, thereby improving its capacity performance and cycle life. It achieves high reversible specific capacity, excellent cycle stability, and improved operating voltage, laying a theoretical foundation for the design and development of flexible, high-performance organic cathode materials.
[0017] The preparation method of the present invention is simple and easy to operate. The prepared composite material is in the form of a film. The film is a self-supporting material and can be directly used as an electrode material without the need for conductive agents, binders and current collectors. Attached Figure Description
[0018] Figure 1 The images show the macroscopic and microscopic morphology of the flexible porous pyrene-tetraketone polyimide composite material in Example 1; where (a) is a macroscopic bending experiment image of the flexible porous pyrene-tetraketone polyimide composite film, (b) is a microscopic cross-sectional SEM image of the flexible porous pyrene-tetraketone polyimide composite film, and (c) is a high-magnification SEM image of the microscopic cross-section of the flexible porous pyrene-tetraketone polyimide composite film. Figure 2 The image shows the FTIR spectrum of the flexible porous pyrene tetraketone polyimide composite material in Example 1. Figure 3 The graph shows the lithium storage cycle performance of the flexible porous pyrene-tetraketone polyimide composite material in Example 1 and the pyrene-tetraketone polyimide powder composite material in Comparative Example 1. Detailed Implementation
[0019] In this invention, unless otherwise specified, the raw materials or reagents required for preparation are all commercially available products well known to those skilled in the art.
[0020] This invention provides a method for preparing a flexible porous pyrene tetraketone-based polyimide composite material, comprising the following steps: 2,7-Diaminopyrene-4,5,9,10-tetraketone, aryltetracarboxylic dianhydride, carbon nanotubes and a first solvent were mixed and subjected to a polycondensation reaction to obtain a pyrene-tetraketone-based polyamic acid / carbon nanotube composite liquid. The pyrene-tetraketone polyamic acid / carbon nanotube composite liquid, graphene oxide, and a second solvent were mixed and then subjected to layer-by-layer self-assembly by vacuum filtration to obtain a pyrene-tetraketone polyamic acid composite film. The pyrene-tetraketone-based polyamic acid composite film was heat-treated to obtain a flexible porous pyrene-tetraketone-based polyimide composite material.
[0021] In this invention, 2,7-diaminopyrene-4,5,9,10-tetraketone, aryltetracarboxylic dianhydride, carbon nanotubes and a first solvent are mixed and subjected to a polycondensation reaction to obtain a pyrene-tetraketone-based polyamic acid / carbon nanotube composite liquid.
[0022] In this invention, the preparation of the 2,7-diaminopyrene-4,5,9,10-tetraone preferably includes the following steps: Pyrene, ruthenium trichloride and sodium periodate were dissolved in a mixed solvent and subjected to an oxidation reaction. After cooling to room temperature, the organic phase was separated and collected. The obtained organic phase was rotary evaporated, recrystallized with DMAC, filtered and dried under vacuum to obtain pyrene-4,5,9,10-tetraone. Pyrene-4,5,9,10-tetraone was added to a mixed solution of concentrated sulfuric acid / concentrated nitric acid for nitration. After the reaction was completed, the reaction solution was added dropwise to water for sedimentation and centrifugation to collect the product. After drying in a vacuum drying oven at 65 °C for 24 h, 2,7-dinitropyrene-4,5,9,10-tetraone was obtained. 2,7-Dinitropyrene-4,5,9,10-tetraone and sodium sulfide nonahydrate were added to DMF with a sodium sulfide nonahydrate mass fraction of 0.05 g / mL. The reduction reaction was carried out under argon protection. The resulting product was washed successively with ethyl acetate, methanol, and distilled water. The product was collected by centrifugation and dried in a vacuum drying oven at 65 °C for 24 h. The crude 2,7-diaminopyrene-4,5,9,10-tetraone was purified in carbon disulfide solvent to obtain 2,7-diaminopyrene-4,5,9,10-tetraone.
[0023] In this invention, the molar ratio of pyrene to ruthenium trichloride is preferably 1:0.1~0.5, more preferably 1:0.12~0.45, and even more preferably 1:0.2~0.4; the molar ratio of pyrene to sodium periodate is preferably 1:4~8, more preferably 1:5~8; the mixed solvent is preferably an organic solvent and water, the organic solvent is preferably dichloromethane and acetonitrile, the volume ratio of dichloromethane and acetonitrile is 1:1; the volume ratio of the organic solvent to water is preferably 2:1. This invention does not impose any special limitation on the amount of the mixed solvent; it can be adjusted according to requirements.
[0024] In this invention, the temperature of the oxidation reaction is preferably 30~40 ℃, more preferably 32~38 ℃, and even more preferably 35 ℃; the time is preferably 12~24 h, more preferably 15~21 h, and even more preferably 16~20 h.
[0025] In this invention, the volume ratio of concentrated sulfuric acid (18.4 mol / L) to concentrated nitric acid (14.5 mol / L) in the concentrated sulfuric acid / concentrated nitric acid mixed solution is preferably 1:3~5, more preferably 1:3~4, and even more preferably 1:3; the temperature of the nitration reaction is preferably 80~110 ℃, more preferably 90~100 ℃, and even more preferably 90~95 ℃; the time of the nitration reaction is preferably 6~14 h, more preferably 7~13 h, and even more preferably 8~12 h.
[0026] In this invention, the molar ratio of 2,7-dinitropyrene-4,5,9,10-tetraone and sodium sulfide nonahydrate is preferably 1:4~6, more preferably 1:4~5; the temperature of the reduction reaction is preferably 40°C, and the time is preferably 12~18h, more preferably 13~17h, and even more preferably 14~16h.
[0027] In this invention, the volumes of ethyl acetate, methanol, and distilled water are independently 3 to 5 times the volume of the reaction liquid obtained from the reduction reaction, preferably 3 to 4 times, and more preferably 3 times; based on 0.6 to 0.7 g of the crude 2,7-diaminopyrene-4,5,9,10-tetraone, the volume of carbon disulfide solvent used is preferably 40 to 60 mL, preferably 45 to 55 mL, and more preferably 50 mL.
[0028] In this invention, the aryl tetracarboxylic dianhydride preferably includes pyromellitic dianhydride, naphthalene tetracarboxylic dianhydride, or perylene tetracarboxylic dianhydride.
[0029] In this invention, the molar ratio of 2,7-diaminopyrene-4,5,9,10-tetraone and aryltetracarboxylic dianhydride is preferably 1:1 to 1.5, more preferably 1:1 to 1.3, and even more preferably 1:1.1 to 1.2.
[0030] In this invention, the first solvent is preferably DMSO, NMP, or DMAC, more preferably DMSO. This invention does not impose any particular limitation on the amount of the first solvent; it can be adjusted according to requirements to ensure the reaction proceeds smoothly.
[0031] In this invention, carbon nanotubes are preferably dispersed in a first solvent to obtain a solvent containing carbon nanotubes. Then, 2,7-diaminopyrene-4,5,9,10-tetraone and aryltetracarboxylic dianhydride are added to conduct a polycondensation reaction, yielding a pyrene-tetraone-based polyamic acid / carbon nanotube composite solution. This invention does not impose specific limitations on the carbon nanotube content in the solvent containing carbon nanotubes; the amount can be adjusted according to requirements to meet the requirements described later.
[0032] In this invention, the mass of the carbon nanotubes is preferably 1 to 10% of the mass of pyrene-tetraketone polyamic acid in the pyrene-tetraketone polyamic acid / carbon nanotube composite solution, more preferably 3 to 8%, and even more preferably 5 to 6%.
[0033] In this invention, the content of pyrene-tetraketone polyamic acid in the pyrene-tetraketone polyamic acid / carbon nanotube composite liquid is preferably 3-10 wt%, more preferably 4-8 wt%, and even more preferably 5-6 wt%.
[0034] In this invention, the temperature of the polycondensation reaction is preferably 160~200℃, more preferably 170~200℃, and even more preferably 180~200℃; the time is preferably 12~24h, more preferably 16~24h; and the atmosphere is preferably argon.
[0035] After the polycondensation reaction is completed, the present invention does not perform any processing to obtain a pyrene tetraketone polyamic acid / carbon nanotube composite liquid.
[0036] After obtaining the pyrene-tetraketone polyamic acid / carbon nanotube composite liquid, the present invention mixes the pyrene-tetraketone polyamic acid / carbon nanotube composite liquid, graphene oxide and a second solvent, and performs layer-by-layer self-assembly by vacuum filtration to obtain a pyrene-tetraketone polyamic acid composite membrane.
[0037] In this invention, the second solvent preferably includes methanol, ethanol, or acetone, more preferably ethanol; the mass ratio of pyrene-tetraketone polyamic acid in the graphene oxide and pyrene-tetraketone polyamic acid / carbon nanotube composite liquid is preferably 1~5:10, more preferably 2~4:10, and even more preferably 3:10.
[0038] In this invention, graphene oxide is preferably dispersed in a second solvent, and a pyrene-tetraketone polyamic acid / carbon nanotube composite solution is added to the resulting graphene oxide dispersion, followed by vacuum filtration. This invention does not impose a specific limitation on the concentration of the graphene oxide dispersion; the amount of graphene oxide can be adjusted according to requirements.
[0039] In this invention, the vacuum filtration conditions preferably include: a vacuum degree of -0.03 to -0.1 MPa, more preferably -0.05 to -0.09 MPa, further preferably -0.06 to -0.08 MPa, most preferably -0.07 MPa, and a vacuuming time of 10 to 40 min, more preferably 20 to 30 min, further preferably 23 to 27 min, and most preferably 25 min.
[0040] In this invention, the thickness of the pyrene-tetraketone polyamic acid composite film is preferably 100-200 μm, more preferably 120-180 μm, and even more preferably 150-160 μm.
[0041] After obtaining the pyrene-tetraketone-based polyamic acid composite film, the present invention heat-treats the pyrene-tetraketone-based polyamic acid composite film to obtain a flexible porous pyrene-tetraketone-based polyimide composite material.
[0042] In this invention, the heat treatment temperature is 300~400℃, more preferably 320~380℃, even more preferably 350~360℃, the time is 2~5h, more preferably 2.5~4.5h, even more preferably 3~3.5h, and the atmosphere is argon; the heating rate to the heat treatment temperature is 1~5℃ / min, preferably 2~4℃ / min, even more preferably 3℃ / min.
[0043] The present invention provides a flexible porous pyrene tetraketone-based polyimide composite material prepared by the preparation method described above. The pyrene tetraketone-based polyimide is coated on carbon nanotubes and forms a three-dimensional interconnected porous conductive structure with graphene.
[0044] This invention provides the application of the flexible porous pyrene tetraketone-based polyimide composite material described above as a positive electrode material in lithium-ion batteries. This invention does not impose any particular limitation on the method of application; any method well-known in the art can be used.
[0045] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods described in the embodiments of the present invention are conventional methods.
[0046] Unless otherwise specified, the experimental and testing methods described below are conventional methods; unless otherwise specified, the reagents and raw materials described below are commercially available.
[0047] Example 1
[0048] (1) Dissolve 1.01 g (0.005 mol) of pyrene in a mixed solution of 20 mL dichloromethane and 20 mL acetonitrile, then add 8.75 g (0.04 mol) of sodium periodate, 0.13 g (0.0006 mol) of ruthenium trichloride and 20 mL of deionized water in sequence, mix well and place in an oil bath at 35 °C for oxidation reaction for 20 h. After the reaction is completed, cool to room temperature, extract and collect the organic phase, evaporate by rotary evaporator, recrystallize with DMAC, filter and dry under vacuum to obtain pyrene-4,5,9,10-tetraone; The obtained pyrene-4,5,9,10-tetraone was dissolved in a mixed solution of 20 mL concentrated sulfuric acid (18.4 mol / L) and concentrated nitric acid (14.5 mol / L) (volume ratio of concentrated sulfuric acid to concentrated nitric acid was 1:3). The solution was then placed in an oil bath and heated to 90 °C for 8 h. After the reaction was completed, the reaction solution was added dropwise to 300 mL of deionized water for sedimentation. The product was collected by centrifugation and dried in a vacuum drying oven at 65 °C for 24 h to obtain a yellow 2,7-dinitropyrene-4,5,9,10-tetraone powder. The obtained 2,7-dinitropyrene-4,5,9,10-tetraone powder and sodium sulfide nonahydrate were added to 20 mL of DMF at a molar ratio of 1:4. The mass fraction of sodium sulfide nonahydrate was 0.05 g / mL. The reaction was carried out at 40 °C for 16 h under argon protection. After the reaction was completed, the resulting reaction solution was washed dropwise with 60 mL of ethyl acetate, methanol and distilled water, respectively. The product was collected by centrifugation and dried in a vacuum drying oven at 65 °C for 24 h to obtain 0.64 g of crude 2,7-diaminopyrene-4,5,9,10-tetraone in deep blue color. The crude 2,7-diaminopyrene-4,5,9,10-tetraone was dissolved in 50 mL of carbon disulfide solvent for purification to obtain 0.41 g of pure 2,7-diaminopyrene-4,5,9,10-tetraone. (2) Purified 2,7-diaminopyrene-4,5,9,10-tetraone and pyromellitic dianhydride were added to 10.0 g of DMSO solvent containing carbon nanotubes at a molar ratio of 1:1. The mixture was subjected to polycondensation reaction at 200 °C for 24 h under an argon atmosphere to obtain a pyrene-tetraone-based polyamic acid / carbon nanotube composite solution. The mass of carbon nanotubes was 6% of the mass of pyrene-tetraone-based polyamic acid in the composite solution, and the content of pyrene-tetraone-based polyamic acid in the composite solution was controlled at 5 wt%. (3) The obtained pyrene-tetraketone polyamic acid / carbon nanotube composite liquid and the ethanol dispersion of graphene oxide were mixed (the mass ratio of graphene oxide to pyrene-tetraketone polyamic acid in the composite liquid was 1:2) to form a uniform composite liquid. The composite liquid was then subjected to layer-by-layer self-assembly by vacuum filtration (vacuum degree was -0.07 MPa, vacuum time was 25 min) to obtain a pyrene-tetraketone polyamic acid composite film with a thickness of 150 μm. (4) The prepared pyrene tetraketone polyamic acid composite film was heated to 350 °C at 3 °C / min for 3.5 h under argon protection and then cooled to room temperature to obtain a flexible porous pyrene tetraketone polyimide composite material.
[0049] Example 2
[0050] (1) 2,7-Diaminopyrene-4,5,9,10-tetraone was prepared according to the method of Example 1; (2) The obtained pure 2,7-diaminopyrene-4,5,9,10-tetraone and pyromellitic dianhydride were added to 10.0 g of DMSO solvent containing carbon nanotubes at a molar ratio of 1:1.3. The mixture was subjected to polycondensation reaction at 200 °C for 24 h under an argon atmosphere to obtain a pyrene-tetraone-based polyamic acid / carbon nanotube composite solution. The mass of carbon nanotubes was 6% of the mass of pyrene-tetraone-based polyamic acid in the composite solution, and the content of pyrene-tetraone-based polyamic acid in the composite solution was controlled at 5 wt%. (3) The obtained pyrene-tetraketone polyamic acid / carbon nanotube composite liquid and the ethanol dispersion of graphene oxide were mixed (the mass ratio of graphene oxide to pyrene-tetraketone polyamic acid in the composite liquid was 1:2) to form a uniform composite liquid. The composite liquid was then subjected to layer-by-layer self-assembly by vacuum filtration (vacuum degree was -0.07 MPa, vacuum time was 25 min) to obtain a pyrene-tetraketone polyamic acid composite film with a thickness of 150 μm. (4) The prepared pyrene tetraketone polyamic acid composite film was heated to 300 °C for 3.5 h at 3 °C / min under argon protection, and then cooled to room temperature to obtain a flexible porous pyrene tetraketone polyimide composite material.
[0051] Example 3
[0052] (1) Pure 2,7-diaminopyrene-4,5,9,10-tetraone was obtained according to the method of Example 1.
[0053] (2) The obtained pure 2,7-diaminopyrene-4,5,9,10-tetraone and pyromellitic dianhydride were added to 10.0 g of DMSO solvent containing carbon nanotubes at a molar ratio of 1:1.5. The mixture was subjected to polycondensation reaction at 200 °C for 24 h under an argon atmosphere to obtain a pyrene-tetraone-based polyamic acid / carbon nanotube composite solution. The mass of carbon nanotubes was 6% of the mass of pyrene-tetraone-based polyamic acid in the composite solution, and the content of pyrene-tetraone-based polyamic acid in the composite solution was controlled at 5 wt%. (3) The obtained pyrene-tetraketone polyamic acid / carbon nanotube composite liquid and the ethanol dispersion of graphene oxide were mixed (the mass ratio of graphene oxide to pyrene-tetraketone polyamic acid in the composite liquid was 1:2) to form a uniform composite liquid. The composite liquid was then subjected to layer-by-layer self-assembly by vacuum filtration (vacuum degree was -0.07 MPa, vacuum time was 25 min) to obtain a pyrene-tetraketone polyamic acid composite film with a thickness of 150 μm. (4) The prepared pyrene tetraketone polyamic acid composite film was heated to 400 °C at 3 °C / min for 3.5 h under argon protection, and then cooled to room temperature to obtain a flexible porous pyrene tetraketone polyimide composite material.
[0054] Example 4
[0055] (1) Pure 2,7-diaminopyrene-4,5,9,10-tetraone was obtained according to the method of Example 1; (2) The obtained pure 2,7-diaminopyrene-4,5,9,10-tetraone and pyromellitic dianhydride were added to 10.0 g of DMSO solvent containing carbon nanotubes at a molar ratio of 1:1. The mixture was subjected to polycondensation reaction at 200 °C for 24 h under an argon atmosphere to obtain a pyrene-tetraone-based polyamic acid / carbon nanotube composite solution. The mass of carbon nanotubes was 6% of the mass of pyrene-tetraone-based polyamic acid in the composite solution, and the content of pyrene-tetraone-based polyamic acid in the composite solution was controlled at 5 wt%. (3) The obtained pyrene-tetraketone polyamic acid / carbon nanotube composite liquid and the ethanol dispersion of graphene oxide were mixed (the mass ratio of graphene oxide to pyrene-tetraketone polyamic acid in the composite liquid was 1:3) to form a uniform composite liquid. The composite liquid was then subjected to layer-by-layer self-assembly by vacuum filtration (vacuum degree was -0.07 MPa, vacuum time was 25 min) to obtain a pyrene-tetraketone polyamic acid composite film with a thickness of 150 μm. (4) The prepared pyrene tetraketone polyamic acid composite film was heated to 350 °C for 3.5 h at 3 °C / min under argon protection, and then cooled to room temperature to obtain a flexible porous pyrene tetraketone polyimide composite material.
[0056] Example 5
[0057] (1) Pure 2,7-diaminopyrene-4,5,9,10-tetraone was obtained according to the method of Example 1; (2) The obtained pure 2,7-diaminopyrene-4,5,9,10-tetraone and pyromellitic dianhydride were added to 10.0 g of DMSO solvent containing carbon nanotubes at a molar ratio of 1:1.3. The mixture was subjected to polycondensation reaction at 200 °C for 24 h under an argon atmosphere to obtain a pyrene-tetraone-based polyamic acid / carbon nanotube composite solution. The mass of carbon nanotubes was 6% of the mass of pyrene-tetraone-based polyamic acid in the composite solution, and the content of pyrene-tetraone-based polyamic acid in the composite solution was controlled at 5 wt%. (3) The obtained pyrene-tetraketone polyamic acid / carbon nanotube composite liquid and the ethanol dispersion of graphene oxide were mixed (the mass ratio of graphene oxide to pyrene-tetraketone polyamic acid in the composite liquid was 1:3) to form a uniform composite liquid. The composite liquid was then subjected to layer-by-layer self-assembly by vacuum filtration (vacuum degree was -0.07 MPa, vacuum time was 25 min) to obtain a pyrene-tetraketone polyamic acid composite film with a thickness of 150 μm. (4) The prepared pyrene tetraketone polyamic acid composite film was heated to 300 °C for 3.5 h under argon protection and then cooled to room temperature to obtain a flexible porous pyrene tetraketone polyimide composite material.
[0058] Example 6
[0059] (1) Pure 2,7-diaminopyrene-4,5,9,10-tetraone was obtained according to the method of Example 1.
[0060] (2) The obtained pure 2,7-diaminopyrene-4,5,9,10-tetraone and pyromellitic dianhydride were added to 10.0 g of DMSO solvent containing carbon nanotubes at a molar ratio of 1:1.5. The mixture was subjected to polycondensation reaction at 200 °C for 24 h under an argon atmosphere to obtain a pyrene-tetraone-based polyamic acid / carbon nanotube composite solution. The mass of carbon nanotubes was 6% of the mass of pyrene-tetraone-based polyamic acid in the composite solution, and the content of pyrene-tetraone-based polyamic acid in the composite solution was controlled at 5 wt%. (3) The obtained pyrene-tetraketone polyamic acid / carbon nanotube composite liquid and the ethanol dispersion of graphene oxide were mixed (the mass ratio of graphene oxide to pyrene-tetraketone polyamic acid in the composite liquid was 1:3) to form a uniform composite liquid. The composite liquid was then subjected to layer-by-layer self-assembly by vacuum filtration (vacuum degree was -0.07 MPa, vacuum time was 25 min) to obtain a pyrene-tetraketone polyamic acid composite film with a thickness of 150 μm.
[0061] (4) The prepared pyrene tetraketone polyamic acid composite film was heated to 400 °C at 3 °C / min for 3.5 h under argon protection, and then cooled to room temperature to obtain a flexible porous pyrene tetraketone polyimide composite material.
[0062] Example 7
[0063] (1) Pure 2,7-diaminopyrene-4,5,9,10-tetraone was obtained according to the method of Example 1; (2) The obtained pure 2,7-diaminopyrene-4,5,9,10-tetraone and pyromellitic dianhydride were added to 10.0 g of DMSO solvent containing carbon nanotubes at a molar ratio of 1:1. The mixture was subjected to polycondensation reaction at 200 °C for 24 h under an argon atmosphere to obtain a pyrene-tetraone-based polyamic acid / carbon nanotube composite solution. The mass of carbon nanotubes was 6% of the mass of pyrene-tetraone-based polyamic acid in the composite solution, and the content of pyrene-tetraone-based polyamic acid in the composite solution was controlled at 5 wt%. (3) The obtained pyrene-tetraketone polyamic acid / carbon nanotube composite liquid and the ethanol dispersion of graphene oxide were mixed (the mass ratio of graphene oxide to pyrene-tetraketone polyamic acid in the composite liquid was 1:4) to form a uniform composite liquid. The composite liquid was then subjected to layer-by-layer self-assembly by vacuum filtration (vacuum degree was -0.07 MPa, vacuum time was 25 min) to obtain a pyrene-tetraketone polyamic acid composite film with a thickness of 150 μm. (4) The prepared pyrene tetraketone polyamic acid composite film was heated to 350 °C for 3.5 h at 3 °C / min under argon protection, and then cooled to room temperature to obtain a flexible porous pyrene tetraketone polyimide composite material.
[0064] Example 8
[0065] (1) Pure 2,7-diaminopyrene-4,5,9,10-tetraone was obtained according to the method of Example 1; (2) The obtained pure 2,7-diaminopyrene-4,5,9,10-tetraone and pyromellitic dianhydride were added to 10.0 g of DMSO solvent containing carbon nanotubes at a molar ratio of 1:1.3. The mixture was subjected to polycondensation reaction at 200 °C for 24 h under an argon atmosphere to obtain a pyrene-tetraone-based polyamic acid / carbon nanotube composite solution. The mass of carbon nanotubes was 6% of the mass of pyrene-tetraone-based polyamic acid in the composite solution, and the content of pyrene-tetraone-based polyamic acid in the composite solution was controlled at 5 wt%. (3) The obtained pyrene-tetraketone polyamic acid / carbon nanotube composite liquid and the ethanol dispersion of graphene oxide were mixed (the mass ratio of graphene oxide to pyrene-tetraketone polyamic acid in the composite liquid was 1:4) to form a uniform composite liquid. The composite liquid was then subjected to layer-by-layer self-assembly by vacuum filtration (vacuum degree was -0.07 MPa, vacuum time was 25 min) to obtain a pyrene-tetraketone polyamic acid composite film with a thickness of 150 μm. (4) The prepared pyrene tetraketone polyamic acid composite film was heated to 300 °C for 3.5 h under argon protection and then cooled to room temperature to obtain a flexible porous pyrene tetraketone polyimide composite material.
[0066] Example 9
[0067] (1) Pure 2,7-diaminopyrene-4,5,9,10-tetraone was obtained according to the method of Example 1.
[0068] (2) The obtained pure 2,7-diaminopyrene-4,5,9,10-tetraone and pyromellitic dianhydride were added to 10.0 g of DMSO solvent containing carbon nanotubes at a molar ratio of 1:1.5. The mixture was subjected to polycondensation reaction at 200 °C for 24 h under an argon atmosphere to obtain a pyrene-tetraone-based polyamic acid / carbon nanotube composite solution. The mass of carbon nanotubes was 6% of the mass of pyrene-tetraone-based polyamic acid in the composite solution, and the content of pyrene-tetraone-based polyamic acid in the composite solution was controlled at 5 wt%. (3) The obtained pyrene-tetraketone polyamic acid / carbon nanotube composite liquid and the ethanol dispersion of graphene oxide were mixed (the mass ratio of graphene oxide to pyrene-tetraketone polyamic acid in the composite liquid was 1:4) to form a uniform composite liquid. The composite liquid was then self-assembled layer by layer by vacuum filtration (vacuum degree was -0.07 MPa, vacuum time was 25 min) to obtain a pyrene-tetraketone polyamic acid composite film with a thickness of 150 μm.
[0069] (4) The prepared pyrene tetraketone polyamic acid composite film was heated to 400 °C at 3 °C / min for 3.5 h under argon protection, and then cooled to room temperature to obtain a flexible porous pyrene tetraketone polyimide composite material.
[0070] Example 10
[0071] The difference between Example 10 and Example 1 is that in step (2), the mass of carbon nanotubes is 3% of the mass of pyrene tetraketone polyamic acid in the composite solution, and the other operations are the same as in Example 1.
[0072] Example 11
[0073] The difference between Example 11 and Example 2 is that in step (2), the mass of carbon nanotubes is 3% of the mass of pyrene tetraketone polyamic acid in the composite solution, and the other operations are the same as in Example 2.
[0074] Example 12
[0075] The difference between Example 12 and Example 3 is that in step (2), the mass of carbon nanotubes is 3% of the mass of pyrene tetraketone polyamic acid in the composite solution, and the other operations are the same as in Example 3.
[0076] Comparative Example 1
[0077] (1) Pure 2,7-diaminopyrene-4,5,9,10-tetraone was obtained according to the method of Example 1; (2) The obtained pure 2,7-diaminopyrene-4,5,9,10-tetraone and pyromellitic dianhydride were added to 10.0 g of DMSO solvent containing carbon nanotubes at a molar ratio of 1:1. The mixture was subjected to polycondensation reaction at 200 °C for 24 h under an argon atmosphere to obtain a pyrene-tetraone-based polyamic acid / carbon nanotube composite solution. The mass of carbon nanotubes was 6% of the mass of pyrene-tetraone-based polyamic acid in the composite solution, and the content of pyrene-tetraone-based polyamic acid in the composite solution was controlled at 5 wt%. (3) The obtained pyrene-tetraketone polyamic acid / carbon nanotube composite liquid and the ethanol dispersion of graphene oxide were mixed (the mass ratio of graphene oxide to pyrene-tetraketone polyamic acid in the composite liquid was 1:2) to form a uniform composite liquid. The composite liquid was uniformly coated on a glass slide and dried under vacuum at 80°C for 12 h. Then, it was heated to 350°C at 3°C / min under an argon atmosphere for 3.5 h to obtain pyrene-tetraketone polyimide composite powder.
[0078] (4) The pyrene tetraketone polyimide composite powder obtained in step (3) is coated on aluminum foil to form an electrode. The dried electrode is then assembled into a lithium-ion battery to test its lithium storage performance.
[0079] Comparative Example 2
[0080] (1) Pure 2,7-diaminopyrene-4,5,9,10-tetraone was obtained according to the method of Example 1; (2) The obtained pure 2,7-diaminopyrene-4,5,9,10-tetraone and pyromellitic dianhydride were added to 10.0 g of DMSO solvent containing carbon nanotubes at a molar ratio of 1:1. The mixture was subjected to polycondensation reaction at 200 °C for 24 h under an argon atmosphere to obtain a pyrene-tetraone-based polyamic acid / carbon nanotube composite solution. The mass of carbon nanotubes was 6% of the mass of pyrene-tetraone-based polyamic acid in the composite solution, and the content of pyrene-tetraone-based polyamic acid in the composite solution was controlled at 5 wt%. (3) The obtained pyrene tetraketone polyamic acid / carbon nanotube composite liquid was uniformly coated on a glass slide, dried under vacuum at 80°C for 12 h, and then treated at 350°C for 3.5 h under argon atmosphere with a heating rate of 3 °C / min to obtain pyrene tetraketone polyimide composite powder. (4) The pyrene tetraketone polyimide composite powder obtained in step (3) is coated on aluminum foil to form an electrode. The dried electrode is then assembled into a lithium-ion battery to test its lithium storage performance.
[0081] Comparative Example 3
[0082] (1) Pure 2,7-diaminopyrene-4,5,9,10-tetraone was obtained according to the method of Example 1; (2) The obtained pure 2,7-diaminopyrene-4,5,9,10-tetraone and pyromellitic dianhydride were added to 10.0 g of DMSO solvent containing graphene oxide at a molar ratio of 1:1. The mixture was subjected to polycondensation reaction at 200 °C for 24 h under an argon atmosphere to obtain a pyrene-tetraone-based polyamic acid / graphene oxide composite solution. The mass ratio of graphene oxide to pyrene-tetraone-based polyamic acid in the composite solution was 1:2, and the content of pyrene-tetraone-based polyamic acid in the composite solution was controlled at 5 wt%. (3) The obtained pyrene tetraketone polyamic acid / graphene oxide composite liquid was uniformly coated on a glass slide, dried under vacuum at 80°C for 12 h, and then treated at 350°C for 3.5 h under argon atmosphere by heating at 3 °C / min to obtain pyrene tetraketone polyimide composite powder. (4) The pyrene tetraketone polyimide composite powder obtained in step (3) is coated on aluminum foil to form an electrode. The dried electrode is then assembled into a lithium-ion battery to test its lithium storage performance.
[0083] Comparative Example 4
[0084] (1) Pure 2,7-diaminopyrene-4,5,9,10-tetraone was obtained according to the method of Example 1; (2) The obtained pure 2,7-diaminopyrene-4,5,9,10-tetraone and pyromellitic dianhydride were added to 10.0 g of DMSO solvent at a molar ratio of 1:1, and polycondensation was carried out at 200 °C for 24 h under an argon atmosphere to obtain a pyrene-tetraone polyamic acid solution. The content of pyrene-tetraone polyamic acid in the solution was controlled at 5 wt%. (3) The obtained pyrene tetraketone polyamic acid solution was uniformly coated on a glass slide, dried under vacuum at 80°C for 12 h, and then heated to 350°C at 3°C / min for 3.5 h under an argon atmosphere to obtain pyrene tetraketone polyimide powder; (4) The pyrene tetraketone polyimide powder obtained in step (3) is coated on aluminum foil to form an electrode. The dried electrode is then assembled into a lithium-ion battery to test its lithium storage performance.
[0085] Characterization and performance testing
[0086] 1) Figure 1 The images show the macroscopic and microscopic morphology of the flexible porous pyrene-tetraketone polyimide composite material in Example 1. (a) is a macroscopic bending test image of the flexible porous pyrene-tetraketone polyimide composite film, (b) is a microscopic cross-sectional SEM image of the flexible porous pyrene-tetraketone polyimide composite film, and (c) is a high-magnification SEM image of the microscopic cross-section of the flexible porous pyrene-tetraketone polyimide composite film. The SEM results show that the pyrene-tetraketone polyimide composite film prepared in Example 1 has a three-dimensional interconnected porous structure, and the bending test image shows that it is flexible.
[0087] 2) Figure 2 The image shows the FTIR spectrum of the flexible porous pyrene tetraketone polyimide composite material in Example 1. Figure 2 The FTIR test results show that the flexible porous pyrene tetraketone-based polyimide composite material prepared in Example 1 has a filtration efficiency of 1774 cm⁻¹. -1 1709 cm -1 The vibrational peak at 1372 cm⁻¹ is attributed to the symmetric and asymmetric vibrational absorption peaks of the carbonyl (C=O) and ketone groups of the pyrene-tetraketone polyimide ring; -1 The vibrational peak at 1124 cm⁻¹ is attributed to the absorption vibration of the CN bond in the pyrene-tetrone polyimide ring; -1 The vibrational peak at that location is attributed to the absorption peak of the pyrene tetraketone unit. This characteristic infrared vibrational peak fully demonstrates the successful preparation of the pyrene tetraketone-based polyimide composite material.
[0088] 3) Pyrenetetrone-based polyimide composite film materials prepared in different cases were directly assembled into lithium-ion batteries, and their lithium storage performance was tested on the Blue Electric testing system. The results are shown in [Figure number missing]. Figure 3 See Table 1.
[0089] Figure 3The lithium storage cycle performance diagrams are shown for the flexible porous pyrene tetraketone polyimide composite material in Example 1 and the pyrene tetraketone polyimide powder composite material in Comparative Example 1. Figure 3 The results show that the flexible porous pyrene tetraketone polyimide composite material prepared in Example 1 has excellent reversible specific capacity and stable cycling performance. After 200 cycles at a current density of 200 mA / g, it can still maintain 97.2% of the initial specific capacity.
[0090] The lithium storage performance of the composite materials prepared in Examples 1-12 and Comparative Examples 1-4 is shown in Table 1.
[0091] Table 1. Lithium storage performance test results of pyrene tetraketone-based polyimide composites in Examples 1-12 and Comparative Examples 1-4.
[0092] From Table 1 and Figure 3 The test results show that the porous pyrene-tetraketone polyimide composite film prepared by this invention effectively improves the conductivity of pyrene-tetraketone polyimide and the utilization of active functional groups (C=O) due to the formation of a three-dimensional interconnected porous structure, enhances the diffusion and adsorption of electrolyte ions, and achieves excellent reversible specific capacity and cycle stability of pyrene-tetraketone polyimide. It is an ideal high-performance flexible green lithium-ion battery cathode material.
[0093] As can be seen from the above embodiments, the flexible porous pyrene tetraketone-based polyimide composite membrane material obtained by the present invention has good mechanical flexibility and conductivity, excellent reversible specific capacity and cycle stability, and is an ideal high-performance flexible green lithium-ion battery cathode material.
[0094] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a flexible porous pyrene tetraketone-based polyimide composite material, characterized in that, Includes the following steps: 2,7-Diaminopyrene-4,5,9,10-tetraketone, aryltetracarboxylic dianhydride, carbon nanotubes and a first solvent were mixed and subjected to a polycondensation reaction to obtain a pyrene-tetraketone-based polyamic acid / carbon nanotube composite liquid. The pyrene-tetraketone polyamic acid / carbon nanotube composite liquid, graphene oxide, and a second solvent were mixed and then subjected to layer-by-layer self-assembly by vacuum filtration to obtain a pyrene-tetraketone polyamic acid composite film. The pyrene-tetraketone-based polyamic acid composite film was heat-treated to obtain a flexible porous pyrene-tetraketone-based polyimide composite material. The aryl tetracarboxylic dianhydride is pyromellitic dianhydride; The mass of the carbon nanotubes is 1-10% of the mass of pyrene-tetraketone polyamic acid in the carbon nanotube composite solution; The mass ratio of pyrene-tetraketone polyamic acid in the graphene oxide and pyrene-tetraketone polyamic acid / carbon nanotube composite solution is 1~5:
10.
2. The preparation method according to claim 1, characterized in that, The first solvent includes DMSO, NMP or DMAC; the molar ratio of the 2,7-diaminopyrene-4,5,9,10-tetraone and aryltetracarboxylic dianhydride is 1:1 to 1.
5.
3. The preparation method according to claim 2, characterized in that, The polycondensation reaction is carried out at a temperature of 160-200°C for 12-24 hours in an argon atmosphere.
4. The preparation method according to claim 1, characterized in that, The second solvent includes methanol, ethanol, or acetone.
5. The preparation method according to claim 1 or 4, characterized in that, The conditions for vacuum filtration include: a vacuum degree of -0.03 to -0.1 MPa and a vacuuming time of 10 to 40 minutes.
6. The preparation method according to claim 5, characterized in that, The thickness of the pyrene tetraketone polyamic acid composite film is 100~200μm.
7. The preparation method according to claim 1, characterized in that, The heat treatment temperature is 300~400℃, the time is 2~5h, and the atmosphere is argon; the heating rate to the heat treatment temperature is 1~5℃ / min.
8. The flexible porous pyrene tetraketone-based polyimide composite material prepared by the preparation method according to any one of claims 1 to 7, characterized in that, Pyrene tetraketone polyimide is coated on carbon nanotubes and forms a three-dimensional interconnected porous conductive structure with graphene.
9. The application of the flexible porous pyrene tetraketone-based polyimide composite material of claim 8 as a positive electrode material in lithium-ion batteries.